Architecture and town planning in the north - Erskine, Ralph (Polar Record, 1968)
When considering the problems of building in the north to talk of an architecture of climate would be to tell only half of the story. It is people in the climate, the cities and the landscape, in families or crowds that count. Ordinary people, not architects, people who sometimes are born in the north and know it and love it or hate it, other people who are moving from more populous areas to small isolated communities in the wilderness, and must be given the amenities they previously enjoyed.